PIP4K2B is mechanoresponsive and controls heterochromatin-driven nuclear softening through UHRF1 - Alessandro Poli; Fabrizio A. Pennacchio; Andrea Ghisleni; Mariagrazia di Gennaro; Margaux Lecacheur; Paulina Nastały; Michele Crestani; Francesca M. Pramotton; Fabio Iannelli; Galina Beznusenko; Alexander A. Mironov; Valeria Panzetta; et al. (Nature Communications, 2023)
PIP4Ks are phosphoinositide kinases often dysregulated in cancer. Here Poli and colleagues find that PIP4K2B is downregulated on soft substrates, and its depletion leads to altered nuclear mechanical properties and defects in cell spreading and motility.